P241 Fertility success rates in adult males with cystic fibrosis. (12th November 2019) - Wilkinson, J; Bianco, B; Bright- Thomas, R; Akhtar, M; Heck, A; Webb, AK
Abstract : Introduction: Approximately 99% of men with cystic fibrosis (CF) are born with congenital bilateral absence of the vas deferens (CBAVD). This results in obstructive azoospermia and infertility, however sperm production remains normal in the vast majority of men. Assisted reproductive technology (ART) methods use surgical sperm retrieval (SSR) to aspirate motile sperm followed by intracytoplasmic sperm injection (ICSI) and implantation to achieve biological parenthood. The aim of this project was to examine ART success rates in men with CF at a large UK adult CF centre over the last 20 years. Method: Data for all male patients referred to a large UK regional fertility centre were retrospectively reviewed. Demographic data, body mass index (BMI kg/m 2 ), forced expiratory volume in one second percent predicted (ppFEV1 ), SSR, ICSI, implantation and pregnancy outcomes were recorded. Results: 50 male patients were referred from an adult CF centre to one fertility centre between 1999–2019. Mean (range) age was 30.1yrs (23- 41yrs). Mean (range) ppFEV1 was 67.5 (25.6–114.8). Mean (range) BMI was 24 (17.1 –36.7). 40 (80%) patients completed fertility treatment. 40/40 (100%) had viable sperm retrieved by SSR. 38/40 couples proceeded to ICSI and implantation (2 chose not to proceed yet). 32/38 (84.2%) couples had established pregnancy as evidenced by foetal heartbeat at 7 weeks. 30/38 (78.9%) couples have, to date, delivered healthy newborns with no reported genetic abnormalities (2 pregnancies ongoing). Conclusion: Increasing CF adult survival and advances in ART mean that for men with CF and their partners biological parenthood is now commonplace. SSR and ICSI IVF are highly effective fertility treatment options for men with CF related CBAVD.